Saliva is a reliable tool to detect SARS-CoV-2. Issue 1 (July 2020) - Azzi, Lorenzo; Carcano, Giulio; Gianfagna, Francesco; Grossi, Paolo; Gasperina, Daniela Dalla; Genoni, Angelo; Fasano, Mauro; Sessa, Fausto; Tettamanti, Lucia; Carinci, Francesco; Maurino, Vittorio; Rossi, Agostino; et al.
Highlights: Saliva is a reliable tool to detect SARS-Cov-2 by RT-rPCR analysis. Saliva may provide information about the clinical evolution of the disease. Saliva could represent a valid instrument in COVID-19 diagnosis. Patients should be checked for salivary viral load at hospital discharge. Summary: Objectives: This study analyzed salivary samples of COVID-19 patients and compared the results with their clinical and laboratory data. Methods: Salivary samples of 25 COVID-19 patients were analyzed by rRT-PCR. The following data were collected: age, sex, comorbidities, drugs. Lactate dehydrogenase (LDH) and ultrasensitive reactive C protein (usRCP) values were registered on the same day when a salivary swab was collected. Prevalence of positivity in saliva and association between clinical data and the cycle threshold as a semiquantitative indicator of viral load were considered. Results: Twenty-five subjects were recruited into this study, 17 males and 8 females. The mean age was 61.5 +/− 11.2 years. Cardiovascular and/or dysmetabolic disorders were observed in 65.22% of cases. All the samples tested positive for the presence of SARS-CoV-2, while there was an inverse association between LDH and Ct values. Two patients showed positive salivary results on the same days when their pharyngeal or respiratory swabs showed conversion. Conclusions: Saliva is a reliable tool to detect SARS-CoV-2. The role of saliva in COVID-19 diagnosis could not be limited to a qualitative detection of the virus, but it may also provide information about the clinical evolution of the disease.